Online Text Processing: A Study of Iranian EFL Learners’ Vocabulary Knowledge - Ahangar, Abbas Ali; Izadi, Mehri (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The internet has developed into an important source of knowledge in recent times. It is used not just for engaging and entertaining users, but also for promoting language learning, especially for English as a Second/Foreign Language (ESL and EFL) learners spending long hours using internet, 85% of all web pages are in English. This experimental research investigated EFL learners’ experiences of vocabulary learning while surfing and text processing. In this small-scale study, two homogeneous groups of EFL learners (N=19), after taking a vocabulary test to ensure that their vocabulary knowledge differences were not significant, were randomly assigned to attend Interchange 3 class in two different groups – one as the Experimental and the other as the Control Group. Each session, there was a free discussion on special topics; while the Experimental Group surfed the internet, processed the online texts, shared and discussed their findings and beliefs on the internet, the Control Group did not use the internet and simply shared their opinions and discussed their personal beliefs. The results of the vocabulary pre- and post-tests indicated that the “internet users” significantly outperformed the “non-internet users”, that is, the Control Group. Based on the findings, internet creates a stimulating environment which helps learners effectively boost their vocabulary knowledge.